Functional performance of upper limb and quality of life after sentinel lymph node biopsy of breast cancer - Velloso,Fernanda S. B. (2011)
BACKGROUND: Sentinel lymph node biopsy (SLNB) is commonly used for the treatment of breast cancer with minimal surgical intervention as well as with low morbidity rates of upper limbs. OBJECTIVES: The aim of the present study was to investigate possible impairments and functional performance of the upper limb on activities of daily living (ADL) and health related quality of life (HRQL) among women treated through SLNB in a Brazilian hospital and to study the association among these variables. METHODS: Forty-five women (58.9±9.3 years) participated in this descriptive, cross-sectional and correlational study. The visual analogue scale (VAS) was used to quantify pain intensity/discomfort, arm circumference and shoulder range of motion (ROM) measurement were used to measure upper limb impairments. The Disabilites of Arm Shoulder and Hand questionnaire (DASH) was used to quantify functional performance of upper limb during ADL and European Organisation for Research and Treatment of Cancer - Quality of Life Questionnaire - Cancer 30 (EORTC-QLQ-C30) and European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire - Breast Cancer Module 23 (EORTC-BR23) were used to characterize HRQL. RESULTS: Results revealed a 75% prevalence of symptoms affecting upper limb (pain or discomfort in arm, shoulder) or breast, although the severity of the symptoms was only mild. Only 4.4% exhibited lymphedema and no ROM restriction was observed. There was little limitation in functional performance of the upper limb, which was associated with Arm Symptoms scale (EORTC BR-23). Impairments and functional performance of upper limb did not interfere on HRQL perception, which was considered to be good. CONCLUSION: SLNB caused small impairments and limitation on the functional performance of the upper limb during ADL and did not influence HRQL in our sample.